Structural Basis of Glycan Recognition of Rotavirus - Sun, Xiaoman; Li, Dandi; Duan, Zhaojun (Frontiers in Molecular Biosciences, 2021)
Rotavirus (RV) is an important pathogen causing acute gastroenteritis in young humans and animals. Attachment to the host receptor is a crucial step for the virus infection. The recent advances in illustrating the interactions between RV and glycans promoted our understanding of the host range and epidemiology of RVs. VP8*, the distal region of the RV outer capsid spike protein VP4, played a critical role in the glycan recognition. Group A RVs were classified into different P genotypes based on the VP4 sequences and recognized glycans in a P genotype-dependent manner. Glycans including sialic acid, gangliosides, histo-blood group antigens (HBGAs), mucin cores have been reported to interact with RV VP8*s. The glycan binding specificities of VP8*s of different RV genotypes have been studied. Here, we mainly discussed the structural basis for the interactions between RV VP8*s and glycans, which provided molecular insights into the host recognition and tropism, offering new clues to the design of RV vaccine and anti-viral agents.